Heat Transfer from an Immersed Heater in Liquid – Liquid – Solid Fluidized Beds - Balasim A. Abid; Majid I. Abdul-Wahab; Asrar A. Al-Obaidy (Engineering and Technology Journal, 2009)
Heat transfer from an immersed heating surface to a liquid-solid and liquid-liquidsolid fluidized beds have been studied. The experiments were carried out in a (0.22) m column diameter fitted with an axially mounted cylindrical heater heated electrically. The fluidizing medium was water as the continuous phase and kerosene as the dispersed phase. Low density (Ploymethyl-methacrylate) particles were used. Previouspublished heat transfer correlations, obtained for fluidized beds containing highdensity particles, gave significant deviations compared with the present data. New correlations were developed to predict the heat transfer coefficients in liquid-solid and liquid-liquid-solid fluidized beds. The new correlation is, The heat transfer coefficients obtained from the present work were compared with those estimated from other correlations reported in the literature. The comparison shows a good agreement with the data obtained for the gas-liquid-solid fluidized beds using low-density particles.